2014
DOI: 10.1177/1098611114561305
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Sustainability of Pattern or Practice Police Misconduct Reform

Abstract: Section 14141 of the Violent Crime Act of 1994 fundamentally restructures the regulation of police behavior in the United States. Since the law’s passage, dozens of police departments have undergone lengthy and complex reforms designed to eliminate a pattern or practice of misconduct. Despite the program’s wide application, neither scholars nor practitioners know much about the efficacy or sustainability of these reforms. This article draws on longitudinal data across several outcome metrics, including citizen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 18 publications
0
44
0
2
Order By: Relevance
“…In other words, policies designed to guide and constrain officers' discretion in the use of less-lethal force can be coupled with practice, so long as police managers and supervisors enforce their department's policy; lax supervision and management concerning the use of force is liable to leave policy loosely coupled with officers' practices. One success story of change in this regard appears to be Cincinnati, whose officers' rates of using force declined following reforms to which the police department agreed in a settlement with DOJ in 2002 (Schatmeier 2013;Chanin 2015); we consider the experience of Cincinnati further in chapter 10.…”
Section: Public Accountabilitymentioning
confidence: 99%
“…In other words, policies designed to guide and constrain officers' discretion in the use of less-lethal force can be coupled with practice, so long as police managers and supervisors enforce their department's policy; lax supervision and management concerning the use of force is liable to leave policy loosely coupled with officers' practices. One success story of change in this regard appears to be Cincinnati, whose officers' rates of using force declined following reforms to which the police department agreed in a settlement with DOJ in 2002 (Schatmeier 2013;Chanin 2015); we consider the experience of Cincinnati further in chapter 10.…”
Section: Public Accountabilitymentioning
confidence: 99%
“…But these superficial indicators cannot be used to measure department-wide institutionalization of community policing as a policy and practice, which appears to be the exception rather than the rule. We do know, however, that at least a few police departments have made substantial changes in the recent past in the direction of a more community-oriented model (e.g., Chanin 2015;Greene 1999;Lowery 2015;Stone et al 2009;Zernikeaug 2014).…”
mentioning
confidence: 97%
“…The record is mixed for departments that have undergone a Justice Department pattern-or-practice investigation and then introduced the mandated reforms (Chanin 2015;Walker 2012). Some of the departments that have complied and instituted reforms have made clear progress, while others have had difficulty sustaining the reforms after the period of DOJ oversight has ended.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Stone et al [2009] found that the Los Angeles Police Department consent decree improved both the quantity and quality of policing while reducing crime. Chanin [2015] studies the effect of police reforms in Pittsburgh, Washington D.C.,…”
Section: Discussionmentioning
confidence: 99%